Protocol for the development of a core domain set for hidradenitis suppurativa trial outcomes. Issue 2 (20th February 2017) - Thorlacius, Linnea; Ingram, John R; Garg, Amit; Villumsen, Bente; Esmann, Solveig; Kirby, Joslyn S; Gottlieb, Alice B; Merola, Joseph F; Dellavalle, Robert; Christensen, Robin; Jemec, Gregor B E
Abstract : Introduction: Randomised controlled trials (RCTs) should have well-defined primary and secondary outcomes to answer questions generated by the main hypotheses. However, for the chronic, inflammatory skin disease hidradenitis suppurativa (HS), the reported outcome measures are numerous and diverse. A recent systematic review found a total of 30 outcome measure instruments in 12 RCTs. This use of a broad range of outcome measures can increase difficulties in interpretation and comparison of results and may potentially obstruct appropriate evidence synthesis by causing reporting bias. One strategy for dealing with these problems is to develop a core outcome set (COS). A COS is a list of outcomes that are meant as mandatory and should be measured and reported in all clinical trials. The aim of this study is to develop a COS for the management of HS. Method and analysis: An international steering group of researchers, clinicians and a patient research partner will guide the COS development. 6 stakeholder groups are involved: patients, dermatologists, surgeons, nurses, industry representatives and drug regulatory authorities. A 1:1 ratio of patients:healthcare professionals is aimed for. The initial list of candidate items will be obtained by combining three data sets: (1) a systematic review of the literature, (2) US and Danish qualitative interview studies involving patients with HS and (3) an online healthcare professional (HCP) item generation survey. To reach consensus on the COS, 4 anonymous online Delphi rounds are then planned together with 2 face-to-face consensus meetings (1 in Europe and 1 in the USA) to ensure global representation. Ethics and dissemination: The study will be performed according to the Helsinki declaration. All results from the study, including inconclusive or negative results, will be published in peer-reviewed indexed journals. The study will involve different stakeholder groups to ensure that the developed COS will be suitable and well accepted.